2008
DOI: 10.1093/jac/dkn501
|View full text |Cite
|
Sign up to set email alerts
|

Furanones, potential agents for preventing Staphylococcus epidermidis biofilm infections?

Abstract: Furanones may inhibit biofilm formation through interference with quorum sensing and thus represent promising agents for protecting surfaces from being colonized by S. epidermidis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 40 publications
2
69
0
1
Order By: Relevance
“…AI-2 signaling in Gram-positive bacteria is even less clear, since no signaling pathways have been described, yet staphylococcal biofilms were inhibited from growing on materials used in medical devices when furanone compounds were integrated into them (252). Likewise, synthetic furanones and furanone analogues incorporating thiophenone moieties decreased staphylococcal biofilm formation mediated by AI-2 (245,253). However, these reports are in conflict with findings that luxS mutants of Staphylococcus epidermidis display increased biofilm formation (254) and that furanones supplied at sub-MICs actually enhance biofilm development (255).…”
Section: Natural-product Qs Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…AI-2 signaling in Gram-positive bacteria is even less clear, since no signaling pathways have been described, yet staphylococcal biofilms were inhibited from growing on materials used in medical devices when furanone compounds were integrated into them (252). Likewise, synthetic furanones and furanone analogues incorporating thiophenone moieties decreased staphylococcal biofilm formation mediated by AI-2 (245,253). However, these reports are in conflict with findings that luxS mutants of Staphylococcus epidermidis display increased biofilm formation (254) and that furanones supplied at sub-MICs actually enhance biofilm development (255).…”
Section: Natural-product Qs Inhibitorsmentioning
confidence: 99%
“…Taking the data together, furanones appear not to inhibit LuxR activation by a "classic" competition mechanism, but rather they appear to engage LuxR at sites that are somewhat different from those used in AHL interactions and thus cause protein instability. Less is clear on how furanones interfere with AI-2-based signaling, though covalent modification of LuxS by C-2 has been implicated (147) (see "Inhibition of AI-2 Production" above) and may explain findings of reduced AI-2 production by this compound in some species (251,253). To date, no studies have investigated if AI-2-binding proteins are directly affected by furanones.…”
Section: Natural-product Qs Inhibitorsmentioning
confidence: 99%
“…11 Many studies have been designed to evaluate the effects of halogenated furanones on eukaryotic cell viability, and there was few data reported the toxicity of halogenated furanones. 12,13 On the aforementioned basis, halogenated furanone compounds have been considered as potential and ideal antibacterial agents for medical device coating. 9,12 For the past decade, special attention has been paid to polymeric microsphere/nanoparticles (NPs) for their sustained-release effects.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 On the aforementioned basis, halogenated furanone compounds have been considered as potential and ideal antibacterial agents for medical device coating. 9,12 For the past decade, special attention has been paid to polymeric microsphere/nanoparticles (NPs) for their sustained-release effects. 14,15 Poly(D, L-lactic acid) (PLA) has been widely developed as drug carrier, due to its desirable biocompatibility and biodegradability.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Owing to their advantages, many researchers have suggested that halogenated furanone compounds would potentially be ideal antibacterial agents on implants for preventing biofilm infection. 27,28 However, there have been few relevant reports on how to use halogenated furanone compounds in implants until now.…”
Section: Introductionmentioning
confidence: 99%